Identifying and Prioritizing Drivers Affecting the Future of the Healthcare Supply Chain with a Focus on Fourth-Generation Technologies - Maleki, Mohammad Hasan; Nasrollahi, Mahdi; Mohammadi, Zahra (Journal of Foresight and Health Governance, 2025)
This study aimed to identify and prioritize the key drivers influencing the future of the healthcare supply chain, focusing on the transformative role of fourth-generation (Industry 4.0) technologies. This applied research adopted a multi-method quantitative design integrating the fuzzy Delphi technique, fuzzy hesitant analytic hierarchy process (F-HAHP), and the MARCOS method. Twenty-five potential drivers were initially extracted through a systematic literature review and expert interviews. These drivers were validated for content using Lawshe’s CVR and screened via fuzzy Delphi to eliminate low-relevance items, retaining nine drivers with defuzzified scores above 0.7. Ten experts in healthcare supply chains, futures studies, and Industry 4.0 participated through judgmental sampling. Drivers were subsequently weighted using F-HAHP and prioritized using the MARCOS method based on three criteria: expert expertise, importance intensity, and certainty. The analysis revealed that the most influential future drivers include: developing intelligent decision-support systems for logistics management and medical supplies (score = 0.856), applying artificial intelligence to predict drug demand and optimize the medical equipment supply process (0.799), using big data technology to analyze drug consumption patterns and predict health crises (0.755), employing smart contracts to streamline procurement, purchasing, and payment processes in the healthcare industry (0.699), and combating fraud in distributed medicines through blockchain technology and authenticity verification (0.584). These top-ranked drivers outperformed others such as integrating IoT-enabled medical devices, expanding cloud computing, increasing automated robotic systems, and using blockchain for counterfeiting prevention. The study highlights that deploying advanced Industry 4.0 technologies—particularly AI, big data, smart contracts, and blockchain—will be critical to building resilient, transparent, and efficient healthcare supply chains. Prioritizing these drivers can guide policymakers and healthcare organizations toward strategic investments, enabling proactive crisis response, cost reduction, improved decision-making, and secure supply chain operations.